Lecturers’ Perception of Intercultural Communicative Competence for English Language Teaching - Surianti, Andi; Putro, Nur Hidayanto Pancoro Setyo (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study examines the integration of cultural competence in English Language Teaching (ELT). Despite its importance, lecturers’ understanding of culture remains limited, making it difficult to implement in teaching. This study analyzes lecturers’ knowledge of culture, intercultural competence (IC), and intercultural awareness (ICA) in ELT. A qualitative research method with a case study approach was employed. Data were collected through semi-structured interviews with four English lecturers at IAIN Bone, selected purposively based on their teaching experience and involvement in culture-based instruction. Thematic analysis was used to identify patterns in their understanding and implementation of IC in the classroom. The findings indicate that most lecturers acknowledge the significance of culture and intercultural communicative competence (ICC) in ELT. However, their approaches vary, from merely transmitting cultural information to prioritizing dialects over broader cultural aspects. Some lecturers also adhere to the native speaker (NS) model, which contradicts the ideal integration of IC in an English as a Foreign Language (EFL) classroom. This study recommends training programs for lecturers on IC and ICA and curriculum development emphasizing cultural integration in ELT. Future research could explore more specific teaching approaches and their impact on students’ intercultural competence.